Use of the chimeric anterolateral thigh free flap in lower extremity reconstruction. Issue 8 (14th September 2015) - Kim, Sang Woo; Kim, Kyu Nam; Hong, Joon Pio; Park, Sung Woo; Park, Chae Ri; Yoon, Chi Sun
Abstract : Background: Reconstruction of three‐dimensional lower extremity defects is challenging because the dead space should be filled and the surface defect should be covered to prevent complications. We present our experience using the vastus lateralis muscle‐chimeric anterolateral thigh (ALT) free flap for reconstructing three‐dimensional lower extremity defects. Methods: This report describes 12 cases of three‐dimensional lower extremity defects that were treated via reconstruction using a chimeric ALT free flap between October 2010 and January 2015. The defects involved the foot (10 patients), distal lower leg (1 patient), and proximal lower leg (1 patient). The sizes of the surface defects ranged from 7.5 × 3 cm 2 to 16 × 7 cm 2, and the sizes of the estimated dead spaces ranged from 2 × 3 cm 2 to 8 × 5 cm 2 . The skin and muscle segment sizes were also evaluated. Results: The sizes of the skin flaps ranged from 8 × 4 cm 2 to 17.5 × 8 cm 2, and the sizes of the muscle segments ranged from 2 × 3 cm 2 to 9 × 5 cm 2 . Eleven cases exhibited full flap survival and one case exhibited partial necrosis. The follow‐up periods ranged from 2 months to 38 months. We did not observe any ranges of motion limitations in the hip and knee joints of the operated leg, or any secondary complications (e.g., abscess or prolonged drainage). Conclusions: The vastus lateralis muscle‐chimeric ALT free flap is a useful option for reconstructing three‐dimensional lower extremity defects. © 2015 Wiley Periodicals, Inc. Microsurgery 35:634–639, 2015.